Synthesis And Characterization Of Soft Condensed Materials Cored By Substituted Phenyl And Naphthalene Moieties - Tun Nur Iskandar, Nur Amanina Juniasari (2019)
Four new homologues series of soft condensed materials consisting of biphenyl unit connected to different core systems, namely phenyl and naphthalene have been successfully prepared and characterized. The physical measurement and elemental analysis (CHN microanalysis), FT-IR, 1D and 2D-NMR spectroscopic techniques were employed to elucidate the molecular structures of the synthesized compounds. The liquid crystal properties and thermal behavior of all title compounds were conducted by POM and DSC. The homologues in the first series comprising a phenyl ring armed by a biphenyl unit with various flexible terminal alkoxy chains, OCnH2n+1 (n = 7-12) at one end and the other end was attached by aromatic imine with terminal p-methoxy substituent.